Challenges in Processes of Validation and Comprehension. Issue 5 (4th July 2019) - Singer, Murray
ABSTRACT: There is accumulating evidence that readers continually evaluate the consistency, congruence, and coherence of text by processes of validation. Validation is initiated immediately on stimulus presentation, may proceed nonstrategically, and serves as a criterion for representational updating. However, validation exhibits a variety of deficiencies. Readers tend to overlook presupposed anomalies and are prone to both endorse text misinformation and to retain previously encoded misinformation. Here, several challenges concerning validation processing are considered against the backdrop of refinements of Kintsch's construction-integration model. Predictions about upcoming text might facilitate comprehension but demand validation. Conversely, the spillover of processing beyond the current text segment reflects processes subsequent to construction and integration and likely contributes to validation. This theoretical framework raises questions about the staging of comprehension processes and about their possible automaticity . Certain contemporary theories tend to highlight either the successes or deficiencies of validation, but they exhibit enough convergence to offer the promise of an effective analysis.